2010
DOI: 10.1007/s10552-010-9526-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in DES daughters

Abstract: ObjectiveWe examined long-term risk of cancer in women exposed to diethylstilbestrol (DES) in utero.MethodsA total of 12,091 DES-exposed women in the Netherlands were followed prospectively from December 1992 till June 2008. Cancer incidence was assessed through linkage with the Dutch pathology database (PALGA) and the Netherlands Cancer Registry and compared with the Dutch female population.ResultsA total of 348 medically verified cancers occurred; median age at end of follow-up was 44.0 years. No overall inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…First, there is no evidence of any increased risk of cancer overall. The DES‐Net project from the Netherlands also found no increase in total cancer risk in DES exposed women compared with the general population [Verloop et al, ], and a French study found no increase in risk of cancers other than breast and CCA [Tournaire et al, ]. Thus, we believe that DES exposure is not likely responsible for substantial excess risks of most of the cancer types we were able to evaluate.…”
Section: Discussionmentioning
confidence: 65%
“…First, there is no evidence of any increased risk of cancer overall. The DES‐Net project from the Netherlands also found no increase in total cancer risk in DES exposed women compared with the general population [Verloop et al, ], and a French study found no increase in risk of cancers other than breast and CCA [Tournaire et al, ]. Thus, we believe that DES exposure is not likely responsible for substantial excess risks of most of the cancer types we were able to evaluate.…”
Section: Discussionmentioning
confidence: 65%
“…33 In addition, DES daughters have also been shown to be at increased risk for breast cancer, genital tract abnormalities, complications of pregnancy (eg, ectopic pregnancy, preterm delivery, neonatal death), and melanoma. 3436 DES sons have higher rates of genital tract abnormalities, such as hypospadias, epididymal cysts, and cryptorchidism, than nonexposed male subjects. 37,38 Animal studies and early epidemiologic studies also questioned an increased risk of testicular cancer in DES sons, although there is currently no evidence to support this assertion.…”
Section: Diethylstilbestrolmentioning
confidence: 97%
“…A moderate increase in breast cancer risk has been shown both in women who were treated with DES during pregnancy, and their daughters [82]. Hsu et al have demonstrated that the expression of 82 miRNAs (9.1% of the 898 miRNAs evaluated) were altered in breast epithelial cells when exposed to DES [83].…”
Section: Environmental Chemicals and Mirnamentioning
confidence: 99%